Successful pembrolizumab treatment of microsatellite instability‐high intrahepatic cholangiocarcinoma: A case report. Issue 4 (4th March 2021) - Ikeda, Yuki; Ono, Michihiro; Ohmori, Ginji; Ameda, Saki; Yamada, Michiko; Abe, Tomoyuki; Fujii, Shigeyuki; Fujita, Miri; Maeda, Masahiro
Key Clinical Message: The tumor reduction effect of pembrolizumab is extremely high compared to standard chemotherapy and might show prolonged survival. Therefore, the MSI status should be examined in patients with cholangiocarcinoma. Abstract : Contrast‐enhanced computed tomography (CT) revealed a primary tumor (black arrow) before the initiation of pembrolizumab (A). After three cycles of pembrolizumab, the primary tumor showed a 32% reduction (B). After 14 cycles, the primary tumor shoed a 79% reduction (C).